110k views
2 votes
Factor completely.

81x4-1
A. (3x + 1)(3x - 1)(3x + 1)(3x - 1)
B. 9x?(9x2 - 1)
C. (9x2 + 1)(9x2 - 1)
D. (9x2 + 1)(3x + 1)(3x - 1)
Reset
Next

User Faris
by
6.0k points

1 Answer

3 votes

Answer: Option D


(9x^2+1)(3x+1)(3x-1)

Explanation:

We have the following expression


81x^4-1

We can rewrite the expression in the following way:


(9x^2)^2-1^2

Remember the following property


(a+b)(a-b) = a^2 -b^2

Then in this case
a=(9x^2) and
b=1

So we have that


(9x^2)^2-1^2


(9x^2+1)(9x^2-1)

Now we can rewrite the expression
9x^2 as follows


(3x)^2

So


(9x^2+1)(9x^2-1) =(9x^2+1)((3x)^2-1^2)

Then in this case
a=(3x) and
b=1

So we have that


(9x^2+1)(9x^2-1) =(9x^2+1)((3x)^2-1^2)


(9x^2+1)(9x^2-1) =(9x^2+1)(3x+1)(3x-1)

finally the factored expression is:


(9x^2+1)(3x+1)(3x-1)

User Mwalling
by
6.3k points